Comparison of biomechanical criteria in cycling maximal effort test - Bertucci, W.; Taiar, R.; Toshev, Y.; Letellier, T. (International Journal of Sports Science and Engineering, 2008)
The purpose of this paper was to evaluate a new set of biomechanical parameters for performance assessment in laboratory sprint cycling. Two groups of seven cyclists, one at elite level, the other at regional level, performed sprint tests in seated and standing positions against 0.8 N/kg resistive loads on the T1670 Basic ergo-trainer (Tacx, Netherlands). A classic racing bicycle was equipped with an SRM Training System (Schoberer, Germany). Two sets of biomechanical parameters were defined: one "classical" and one "new" set of parameters. The relation between crank torque and crank angle was carefully studied and a selection of characteristic criteria for assessing the cycling performance was proposed. In order to quantify the differences in the pedalling technique, new criteria were introduced, such as the time interval during which the instantaneous power exceeded 90 % of the maximal power output as a proportion of the pedal downstroke (RMPD90). The results show 1) that the cyclo cross cyclists can generated high level of power output during sprint test (close to 18W/kg) and 2) there is no significant difference between regional level and elite level concerning the set of biomechanical parameters classically employed. However, the new set of biomechanical parameters (RMPD90) revealed differences between the pedalling characteristics of the elite level and regional level groups. The results of the present study suggest that the analysis of the sprint test performed with classical set of biomechanical parameters can be completed using the RMPD90 as a supplementary fitness criterion.